INCREASING STUDENTS’ VOCABULARY BY USING PICTURES AT SMP KRISTEN 17 TATENGESAN - Angel Maringka; Nihta V. F. Liando; Jim Ronny Tuna (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study was to examine whether the use of pictures could increase students' vocabulary. Students of SMP Kristen 17 Tatengesan for the 2022/2023 school year (including 20 students of seventh grade) were selected for this study. Pre-experimental design with one group pre-test and post-test was used in this research. This study consisted in four meetings. Prior to treatment (used pictures), the first researchers performed a pretest. After treatment (used picture), students were given a post-test. Data collection technique used test as instrument. That is objective in terms of matching the item 5 numbers, completion 5 numbers and true/false 10 numbers, The total is 20 numbers. The result of this study found that pictures was effective showed the scores post-test (78.52) was higher those of pre-test (50.5). This suggests that the use of pictures is considered can effectively increase students vocabulary.